Investigation of Grain Growth in Chalcopyrite CuInS2 Photoelectrodes Synthesized under Wet Chemical Conditions for Bias-Free Photoelectrochemical Water Splitting - Chae, Sang Youn; Yoon, Noyoung; Jun, Minki; Hur, Sung Hyun; Lee, Myeongjae; Kim, Bong Soo; Kim, Jin Young; Park, Eun Duck; Park, Jong Hyeok; Joo, Oh Shim (Solar RRL, 2024)
Photoelectrochemical (PEC) cells offer a promising method for producing green hydrogen through the splitting of water using solar energy. However, the cost-effective synthesis of highly crystalline p-type semiconductor materials for PEC cells remains a significant challenge for industrial applications. Herein, a CuInS2 photoelectrode is fabricated using a scalable and economical wet chemical spin-coating technique. To enhance the crystallinity and photoelectrochemical activity of the photoelectrode, the grain size is precisely controlled by adjusting the atomic ratio, thickness, morphology, and Ag doping. Evaluating a novel growth mechanism of CuInS2 from Cu–In–O reveals that Ag doping significantly promotes grain growth. Consequently, the CuInS2 photocathode achieves one of the highest photoelectrochemical activities (−9.8 mA cm−2 at 0 VRHE) reported for CuInS2 photoelectrodes synthesized via wet chemical methods. Bias-free water splitting is achieved using a CuInS2-based photoelectrode in a photovoltaic–PEC cell configuration. These results highlight the potential of CuInS2, prepared through wet chemical methods, for cost-effective photoelectrochemical water splitting.
Keywords: CuInS 2; Green hydrogen; Photoelectrochemical water splitting; Photoelectrochemicals; Photoelectrode; Photovoltaics; Photovoltaic–photoelectrochemical cell; Synthesised; Wet chemicals; CuInS2; green hydrogen; photoelectrochemical cells; photovoltaic–photoelectrochemical cells; spin coating